Testing the Fisher Hypothesis in the G-7 Countries Using I(d) Techniques - Guglielmo Maria Caporale; Luis A. Gil-Alana (Center for Economic Studies and ifo Institute (CESifo), 2017)
This paper revisits the Fisher hypothesis by estimating fractional integration and cointegration models that are more general than the standard ones based on the classical I(0)/I(1) dichotomy. Two sets of results are obtained under the alternative assumptions of white noise and Bloomfield (1973) autocorrelated errors respectively. The univariate analysis suggests than the differencing parameter is higher than 1 for most series in the former case, whilst the unit root null cannot be rejected for the majority of them in the latter case. The multivariate results imply that there exists a positive relationship, linking nominal interest rates to inflation; however, there is no evidence of the full adjustment of the former to the latter required by the Fisher hypothesis.
Keywords: C22; C32; E43; 330; Fisher effect; fractional integration; long memory; G7 countries